2011
DOI: 10.2117/psysoc.2011.119
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceptual and Personal Memory Retrieval on Story Comprehension

Abstract: This study focused on the relationship between personal perceptual memory and story comprehension. In two experiments, participants read story texts. Half the participants were asked to retrieve highly vivid perceptual memories (Exp. 1) or autobiographical memories as highly perceptual and personal memories (Exp. 2) before reading a story, and the other half were asked to retrieve less vivid perceptual memories, as a control task, before reading. Results showed that participants read more slowly under the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The processing of discourse and the generation of emotion inferences have also been found to facilitate that comprehenders experience emotions [72,80,81]. Prior studies suggest that these emotions promote that the comprehender engages with the material [80,82]. Other investigations have highlighted that discourse comprehension can be facilitated when comprehenders are asked to answer elaborative questions (such as 'why do you think that the statement you just read makes sense?'…”
Section: Commentmentioning
confidence: 99%
“…The processing of discourse and the generation of emotion inferences have also been found to facilitate that comprehenders experience emotions [72,80,81]. Prior studies suggest that these emotions promote that the comprehender engages with the material [80,82]. Other investigations have highlighted that discourse comprehension can be facilitated when comprehenders are asked to answer elaborative questions (such as 'why do you think that the statement you just read makes sense?'…”
Section: Commentmentioning
confidence: 99%
“…It is proposed that this finding indicates a particular emotion up-regulation mechanism (see also Menninghaus et al 2017), activated in the observed encounters with negative contents in fiction. In a study conducted by Tsunemi and Kusumi (2011) participants were given a task before reading a short story: one group had to generate perceptually rich personal memories, thus activating self-schema, whereas the other group had to play a word game, a task unrelated to the self. When the researchers compared how much time the participants needed to read the story, they found that reading times increased for those who had generated perceptual memories.…”
Section: Emotional Valence and Personal Relevancementioning
confidence: 99%